The repositories of the Prussian State Library collection in Lower Silesia during the World War II - Kudelski, Jarosław Robert (Saeculum Christianum. Pismo Historyczne, 2021)
German cultural institutions had been conducting preparations to secure their collections in the event of a war since mid-1930s. The Prussian State Library, the holdings of which included the most precious German manuscripts and prints, was one of those institutions. Air attacks carried out on the capital of the Third Reich triggered the decision to evacuate the collection to Thüringen, Brandenburg, Pomerania and Lower Silesia. Largest deposits had been located in the latter. The unique heritage items stored there included medieval manuscripts, prayer books, music autographs and newspaper yearbooks as well as letters and private documents of many prominent representatives of German culture and art. Those items were evacuated, among other places, to Fürstenstein (Książ) Gießmannsdorf (Gościszów), Gröditzburg (Grodziec), Grüssau (Krzeszów), Fischbach (Karpniki) and Hirschberg (Jelenia Góra). The evacuation was conducted in cooperation with the heritage conservator for Lower Silesia, professor Günther Grundmann. With his assistance, in the course of a few years, a unique collection was created in Lower Silesia. Towards the end of the war the collection was deprived of proper care, as the authorities lacked resources to secure it. This resulted in the destruction of some items during military actions. The remaining parts of the collection had been taken over by Polish officials and were transferred to library collections in Krakow, Warszawa, Olsztyn, Toruń, Lublin and Łódź.